Influence of cuff stiffness on hemodynamics and perceived cuff pressure in the upper extremities in males and females: implications for practical blood flow restriction training - Robert Bielitzki; Tom Behrendt; Toan Nguyen; Martin Behrens; Victoria Malczewski; Alexander Franz; Lutz Schega (BMC, 2023)
Abstract Background Practical blood flow restriction (pBFR) during exercise is a cost-saving alternative to traditional blood flow restriction using pneumatic cuffs, particularly when exercising in a group setting. Depending on the pBFR technique, several factors (e.g., cuff width, limb circumference) have already been shown to be of importance when applying the pBFR pressure. Given that elastic cuffs are often used for pBFR, the cuff stiffness might be an additional influencing factor. Therefore, the present study compared the acute effects of three elastic cuffs with identical width but different stiffness (high stiffness (HS), medium stiffness (MS), and low stiffness (LS)) on hemodynamic measures and perceived cuff pressure at rest. Methods In a randomized, counter-balanced cross-over study, 36 young and normotensive participants completed three experimental trials. After a 10-min rest period in supine position, the cuff was loosely and proximally applied to the right upper arm. Following baseline data recording, the cuff was successively tightened in 10%-increments with respect to the limb circumference (%overlap) until arterial blood flow was occluded. At baseline and during each %overlap, systolic peak blood flow velocity of the brachial artery, rating of perceived cuff pressure, as well as muscle oxygen saturation and total hemoglobin concentration of the biceps brachii muscle were recorded. Results The %overlap required to occlude arterial blood flow was different between the three cuffs (HS: 30.9 ± 3.8%, MS: 43.9 ± 6.1%, LS: 54.5 ± 8.3%). Furthermore, at 30% overlap, systolic peak blood flow velocity was lower when applying the HS (9.0 ± 10.9 cm∙s− 1) compared to MS (48.9 ± 21.9 cm∙s− 1) and LS cuff (62.9 ± 19.1 cm∙s− 1). Rating of perceived cuff pressure at 30% overlap was higher when using the HS (6.5 ± 1.5 arbitrary unit (a.u.)) compared to MS (5.1 ± 1.4 a.u.) and LS cuff (4.9 ± 1.5 a.u.) with no difference between the MS and LS cuff. However, muscle oxygen saturation and total hemoglobin concentration were not different between the three cuffs. Conclusions The present study revealed that the cuff stiffness influenced blood flow velocity and arterial occlusion pressure. Therefore, cuff stiffness seems an important factor for the application of pBFR.